Occupational Safety and Health Management at Alumina Ltd - Pavlović, Dragana; Lazic, Dragica; Kešelj, Dragana; Petrović, Zoran; Dragojlović, Dragana; Vasiljević, Nebojša (Journal of Engineering & Processing Management, 2022)
Occupational safety and health (OSH) is an integral part of the organization of work, and includes measures and means necessary to achieve safe working conditions. In terms of the current Law on Occupational Safety and Health of the Republic of Srpska, among other things, the employer is responsible for drafting the Risk Assessment Act. This paper presents a risk assessment for the position of Technological Equipment Operator. The risk assessment was performed, hazards were identified and measures to reduce them were proposed using the modified AUVA method. Jobs with risk rank I and II are considered jobs with acceptable or low risk, i.e. those including risk levels 1-5, and 6-9 respectively. Jobs with increased risk are jobs with a risk rating of medium, high and unacceptable - III, IV and V, i.e. encompassing risk levels 10-12, 15-16 and 20-25, respectively was estimated that the position of the technological equipment operator is a high-risk (IV) position, i.e. a position with difficult working conditions, and a risk of the loss of working ability or impairment of health.